Light availability may control extracellular phosphatase production in turbid environments - Rychtecký, Pavel; Řeháková, Klára; Kozlíková, Eliška; Vrba, Jaroslav (Microbial ecology, 2015)
Extracellular phosphatase production by phytoplankton was investigated in the moderately eutrophic Lipno reservoir, Czech Republic during 2009 and 2010. We hypothesized that production of extracellular phosphatases is an additional mechanism of phosphorus acquisition enabling producers to survive rather than to dominate the phytoplankton. Hence, we examined the relationship between light availability and phosphatase production, as light plays an important role in polymictic environments. Bulk phosphatase activity was measured using a common fluorometric assay, and the production of phosphatases was studied using the Fluorescently Labelled Enzyme Activity technique, which enabled direct microscopic detection of phosphatase-positive cells. In total, 29 taxa of phytoplankton were identified during both years. Only 17 taxa from the total number of 29 showed production of extracellular phosphatases. Species dominating the phytoplankton rarely produced extracellular phosphatases. In contrast, taxa exhibiting phosphatase activity were present in low biomass in the phytoplankton assemblage. Moreover, there was a significant relationship between the proportion of phosphatase positive species in samples and the Z(eu):Z(mix) ratio (a proxy of light availability). A laboratory experiment with different light intensities confirmed the influence of light on production of phosphatases. Our seasonal study confirmed that extracellular phosphatase production is common in low-abundance populations but not in dominant taxa of the phytoplankton. It also suggested the importance of sufficient light conditions for the production of extracellular phosphatases.
Keywords: Phytoplankton; fosfatasy; Light; světlo; Phosphoric Monoester Hydrolases; fytoplankton